Exploring biomarkers and prognostic factors in uterine carcinosarcoma: An insight into L1CAM, CDX2, p53, and MSI status. - Jesse Lopes da Silva; Lucas Zanetti de Albuquerque; Fabiana Resende Rodrigues; Nina Carrossini Bastos; Isabele Avila Small; Elisa Bouret Campos Barroso; Fernando Lopes Cordero; Daniel de Souza Fernandes; Eduardo Paulino; Andreia Cristina de Melo (PLoS ONE, 2023)
Background Uterine Carcinosarcomas (UCS) are a rare type of cancer composed of an admixture of high-grade carcinomatous and sarcomatous elements. Clinicopathological prognostic factors in UCS are well established, but studies that approach the impact of biomarkers in this unusual disease are scarce. The study objective was to evaluate the prevalence and prognostic impact of a panel of prominent biomarkers in uterine carcinosarcoma (UCS) using an immunohistochemical characterization with four biomarkers. Methods and findings The internal database of a single Brazilian institution was carefully explored to select women diagnosed with UCS who were submitted to surgery and postoperative chemotherapy with carboplatin and paclitaxel between January 2012 and December 2017. Tissue microarrays containing UCS samples were evaluated by immunohistochemistry for L1CAM, CDX2, p53 and microsatellite instability markers. A total of 57 cases were included. The mean age was 65.3 years (standard deviation, SD 7.0). L1CAM was negative (score 0, no staining) in 27 (47.4%) patients. Of L1CAM-positive, 10 (17.5%) showed weak (score 1, <10%), 6 (10.5%) showed moderate (score 2, between 10-50%), and 14 (24.6%) showed strong L1CAM staining (score 3, ≧50%). dMMR occurred in 3 (5.3%) cases. The p53 was aberrantly expressed in 15 (26.3%) tumors. CDX2 was positive in 3 (5.3%) patients. The three-year progression-free survival (PFS) rate in the general population of the study was 21.2% (95% CI: 11.7-38.1) and the three-year overall survival (OS) rate was 29.4% (95% CI: 18.1-47.6). By multivariate analysis, the presence of metastases and CDX2-positive were significantly associated with poorer PFS (p < 0.001 and p = 0.002, respectively) and OS (p < 0.001 and p = 0.009, respectively). Conclusion The strong influence of CDX2 on prognosis requires further investigation. Biological or molecular variability may have impaired the assessment of the impact of the other markers on survival.